A user's guide to coping with estuarine management bureaucracy: An Estuarine Planning Support System (EPSS) tool. (February 2018) - Lonsdale, Jemma; Nicholson, Rose; Weston, Keith; Elliott, Michael; Birchenough, Andrew; Sühring, Roxana
Abstract: Estuaries are amongst the most socio-economically and ecologically important environments however, due to competing and conflicting demands, management is often challenging with a complex legislative framework managed by multiple agencies. To facilitate the understanding of this legislative framework, we have developed a GISbased Estuarine Planning Support System tool. The tool integrates the requirements of the relevant legislation and provides a basis for assessing the current environmental state of an estuary as well as informing and assessing new plans to ensure a healthy estuarine state. The tool ensures that the information is easily accessible for regulators, managers, developers and the public. The tool is intended to be adaptable, but is assessed using the Humber Estuary, United Kingdom as a case study area. The successful application of the tool for complex socio-economic and environmental systems demonstrates that the tool can efficiently guide users through the complex requirements needed to support sustainable development. Highlights: An integrated Estuarine Planning Support System (EPSS) tool is presented. The EPSS tool is a decision support tool to aid sustainable management. The EPSS tool incorporates current natural and social science concepts.